Italy and Lega Nord: Stories of Communities, National (Dis)Integration and Spaces of (Restricted) Citizenship - Di Bonaventura, Florence (SocietàMutamentoPolitica, 2016)
This paper focuses on the conception of citizenship of the Italian political party Lega Nord. To that aim, we consider citizenship in terms of belonging to the political community, which thus also defines the boundaries of exclusion. In our approach, citizenship is a structuring dimension of building a political community and it has two components: the State and the nation. By situating these concepts (State, nation and citizenship) in a theoretical-historical framework, we enlighten the conceptions of the Lega Nord in relation to each of them, by positioning them in long term socio-historical dynamics in Italy.